Modeling of money supply using LASSO regression with Cross-Validation - Adelheid Januaviani, Trisha Magdalena; Eman Lesmana, Sukono, (Opción, 2020)
The study aims to investigate the modeling of money supply using LASSO regression with cross-validation. The money supply spent can be applied to multiple regression analysis because it has many influencing factors. Multiple linear regression analysis is a statistical technique to examine the relationship between independent variables and independent variables. As a result, the number of independent variables in the money supply asked is greater than multicollinearity. In conclusion, if net foreign assets consisting of bills and non-residents liabilities in Indonesia have increased by one billion, then the money supply in circulation in Indonesia will decrease by 0.6259048 and 1.451317.